THE EFFECT OF MUSIC THERAPY ON REDUCING ANXIETY OF PRE OPERATIONAL PATIENTS IN SRI PAMELA TEBING HIGH Hospital in 2022 - Kristina Kristina (Institute of Computer Science (IOCS), 2022)
Surgery often causes a stress reaction that affects both physiological and psychological. One of the psychological responses that can be experienced by patients who will undergo surgery is anxiety with a high percentage of 80% which has an impact on delays in surgery, increasing surgical risk. Efforts to overcome anxiety can be done by giving music therapy because it can divert from painful stimuli or negative thoughts associated with surgery, relieve symptoms of anxiety and increase relaxation. For this reason, the authors are interested in examining whether the effect of music therapy on reducing anxiety in pre-operative patients at Sri Pamela Tebing Tinggi Hospital. The purpose of this study was to identify the effect of classical music therapy on reducing the anxiety level of patients who will carry out surgical procedures. The type of research used in this study is a quasi-experimental design using a pre-test and posttest group design. The data collection in this study was carried out in 2 stages. The implementation stage included determining the appropriate respondents to measuring anxiety levels through filling out questionnaires, then intervening in patients by listening to the classical song Mozart Clarinet Concerto In A Major K 622 for 2 cycles and then measuring the level again. worry. The results showed that the majority or patients tended to experience a decrease in anxiety after giving music therapy, where previously as many as 24 people (92, 3%) experienced moderate anxiety which decreased to 12 people (46.2%) after giving music therapy to the category of mild anxiety. Based on the results of this study, it was concluded that Mozart's classical music therapy had a positive effect in reducing the patient's anxiety level. Therefore, the management can apply the music therapy as an alternative nursing intervention in reducing anxiety.